Effect of Information Channels on Covid-19 Vaccine Acceptance among University Students of Rawalpindi/Islamabad: A Cross Sectional Study - Mohsin, Shamaila; Zahoor, Mamoona; Mashhadi, Syed Fawad; Rehman, Muhammad Anees ur; Abbasi, Willma Naeem; Javaid, Rabiah; Imran, Zainab; Faiz, Usama (Pakistan Armed Forces Medical Journal, 2024)
Objectives: To find the effect of information channels on Covid-19 acceptance among university students of Rawalpindi/ Islamabad.Study Design: Cross sectional analytic study.Place and Duration of Study: Study was conducted in four imminent Universities in Rawalpindi/Islamabad, Air University,Rawalpindi Medical University, Riphah University and Quaid-e-Azam University, Rawalpindi, from May to Aug 2022.Methodology: Participants from four universities in Rawalpindi/Islamabad Pakistan, were recruited for this current research from May to August 2022. A sample size of 377±14 was computed using the Rao soft sample size calculator, maintaining a 5% margin of error and a 95% confidence interval a population proportion (50%). Non-probability convenient sampling was used.Data was analysed using SPSS version 26.Results: There were 377 students recruited, out of which majority 207(55%) were female. Most of the students were in the Medicine and allied fields 227(60.2%). Almost, half of the respondents (44.56%) received information about the COVID-19 vaccine from mobile networks. The level of trust in vaccine information was also highest for Mobile Networks (31.30%).Participants' perceptions of the covid 19 risk, 156(41%) revealed high concerns for infecting family and friends with the virus.There was a significant association of female gender (p